Determinants of turnover intention among employees / Hidayati Arshad and Fadilah Puteh - Arshad, Hidayati; Puteh, Fadilah (Universiti Teknologi MARA, Shah Alam, 2015)
High number of turnover rate among employees signals a major weakness towards organizations achievement. This is due to the fact that employees are the key player to determine organizational performance and survival. This study attempts to determine the turnover intention among employees. Employees of Woongjin Coway (M) Sdn Bhd were chosen as subject of interests. Data was collected through questionnaire to 106 employees from four different branches located in the Klang Valley namely Ampang, Cheras, Petaling Jaya and Klang. Stratified random sampling was utilized to reach the minimum number of samples required in this study. SPSS was employed as a tool to aid in analysis of findings. The findings from the study revealed that only two factors namely available job alternatives; and work-life balance have significant impact on employee turnover intention.